Accurate Modeling and Efficiency Optimization of High Frequency BCM Mode Boost Converter Based on GaN Devices - Yifeng Wang; Zhongjie Wang; Bo Chen; Hao Wang (CSEE Journal of Power and Energy Systems)
With further population of gallium nitride (GaN) devices, traditional boost topology has an opportunity to obtain a higher power density with a higher switching frequency. However, high-frequency switching loss of GaN devices has become one important factor restricting improvement of converter efficiency. Aiming at improving efficiency of synchronous rectification boost topology, this paper first discusses advantages of boost converter operating in boundary conduction mode (BCM). In order to fully ensure realization of soft switching in BCM mode, this paper has carried on indepth mathematical modeling analysis to the realization process of soft switching. Conclusion points out implementation range of soft switching can be extended by prolonging conduction time of synchronous rectification. Finally, an experimental prototype with rated power of 500 W is built to verify theoretical analysis. By ensuring implementation of soft switching in BCM mode, peak efficiency of prototype reaches 98.2%. Correctness of theoretical analysis in this paper is verified.